Responder Analysis of a Multicomponent Non-Pharmacological Intervention (MAKS) for People With Cognitive Impairment in the German Day-Care Study (DeTaMAKS) - Luttenberger, Katharina; Grässel, Elmar; Behrndt, Elisa-Marie; Özbe, Dominik; Donath, Carolin; Scheel, Jennifer Felicia (Frontiers in Psychiatry, 2019)
Background: Multicomponent non-pharmacological therapies have been shown to be effective at reducing cognitive symptoms and slowing deterioration in abilities to perform activities of daily living (ADL) in individuals with cognitive impairment. However, little is known about response rates and predictors of response.
CRIS-Team WoS Importer:2019-09-06